Controllable synthesis and luminescent properties of three-dimensional nanostructured CaWO4:Tb3+ microspheres - Tian, Yue; Chen, Baojiu; Yu, Hongquan; Hua, Ruinian; Li, Xiangping; Sun, Jiashi; Cheng, Lihong; Zhong, Haiyang; Zhang, Jinsu; Zheng, Yanfeng; Yu, Tingting; Huang, Libo (Journal of colloid and interface science, 2011)
CaWO4:Tb3+ microspheres assembled by submicrospindles were synthesized via a mild sonochemical route with the aid of surfactant Polyglycol 600. The formation mechanism for the 3D-structured CaWO4:Tb3+ microspheres was studied. [Display omitted] ► Nanostructured CaWO4:Tb3+ microspheres were self-assembled via a sonochemical route with the aid of PEG-600. ► Formation mechanism of the microspheres was proposed based on the ultrasonic irradiation time experiments. ► Energy transfer processes between Tb3+ ions were studied through analysis on the fluorescence decays. Three-dimensional (3D) nanostructured CaWO4:Tb3+microspheres assembled by submicrospindles were synthesized via a mild sonochemical route from an aqueous solution of CaCl2, TbCl3 and Na2WO4 with the aid of surfactant Polyglycol 600 (PEG-600). The crystal structure and morphology of the as-prepared products were characterized by using X-ray diffraction (XRD) and field emission scanning electron microscopy (FE-SEM). Rietveld refinement was carried out on the XRD data. The results showed that the CaWO4:Tb3+nanoparticles can be formed without ultrasonic irradiation or addition of PEG-600. With continuously increasing irradiation time the submicrospindles and microspheres could be self-assembled. The central diameter and length of the submicrospindles are around 190 and 500nm, respectively. The 3D CaWO4:Tb3+nanostructured microspheres with diameter of 2–4μm were assembled by the submicrospindles. A possible formation mechanism for the 3D-structured CaWO4:Tb3+microspheres was proposed. The Photoluminescent (PL) properties of Tb3+ions in the nanostructured CaWO4 microspheres were studied. The energy transfer processes in CaWO4:Tb3+microspheres were analyzed. The electric dipole–dipole energy transfers related to 5D3 level were studied by inspecting the fluorescence decay of 5D3 level. The energy transfer critical distance was estimated.